Effects of home confinement on the intensity of physical activity during the COVID-19 outbreak in team handball according to country, gender, competition level, and playing position: A worldwide study - Hermassi, S.; Bouhafs, E. G.; Bragazzi, N. L.; Ichimura, S.; Alsharji, K. E.; Hayes, L. D.; Schwesig, R. (International Journal of Environmental Research and Public Health, 2021)
This study investigated effects of home confinement on physical activity (PA) in Team Handball during the COVID-19 outbreak. A total of 1359 handball players participated (age: 23 ± 6 years). Participants from Europe, Western Asia, and North Africa answered an online version of the International Physical Activity Questionnaire (IPAQ) considering "before" and "during" confinement. COVID-19 home confinement has had a negative effect on PA (vigorous, moderate, walking, and overall). The largest decrease was in the sum parameter "all PA" (MET (metabolic equivalent of task)-min/week, Etap2 = 0.903; min/week, Etap2 = 0.861). Daily sitting time increased from 2.7 to 5.0 h per weekday (p < 0.001, Etap2 = 0.669). For gender, continent, country, level of handball league, and playing position, no significant differences (group and interaction effects) were observed. The largest change in PA behavior was in walking (minutes per day: Etap2 = 0.755), with males displaying the greatest decrease (from 62 ± 11 to 30 ± 14 min per weekday; d = 2.67). In terms of magnitude, difference between genders was greatest for sitting time (difference in d = 1.20). In conclusion, while COVID-19 measures were essential to preserve public health, PA was compromised and sedentary behavior increased because of these public health measures regardless of gender, playing position, and competition level.